Cryptic Diversity within the Endemic Mekong Giant Earthworm, Amynthas mekongianus (Cognetti, 1922) (Clitellata: Megascolecidae) Across the Lower Mekong River Basin with Descriptions of a New Species - Nantarat, Nattawadee; Panha, Somsak; Chanabun, Ratmanee; Inkhavilay, Khamla; Bantaowong, Ueangfa (Tropical Natural History, 2025)
The Lower Mekong Basin is recognized as a region of remarkable biodiversity. However, it is currently experiencing severe degradation due to rapid economic development and the intensifying effects of climate change. Numerous species, including earthworms, are under increasing threat. In addition, Amynthas mekongianus (Cognetti, 1922) exhibits considerable intraspecific morphological variability, making its identification challenging. Therefore, the study aims to clarify species boundaries within the A. mekongianus complex in the Lower Mekong River Basin using both morphological and molecular approaches. Specimens were collected from multiple sites in the basin, and analyses revealed at least two putative species. Phylogenetic reconstructions (NJ, ML, and BI) together with species delimitation methods (ASAP, GMYC, and bPTP) consistently supported the recognition of two distinct lineages. These lineages differ primarily in body length, segment number, and spermathecae morphology. Accordingly, they are recognized as A. mekongianus sensu stricto and A. sirindhornae Nantarat & Bantaowong, sp. nov., which is formally described herein. This study enhances understanding of the evolutionary complexity and taxonomic status of the group, providing a foundation for future conservation and management strategies in the region.